Synthesis of (–)-Bulgecinine and 5-epi-Bulgecinine through Proline-Catalysed Asymmetric α-Hydroxylation of an Aldehyde Derived from l-Glutamic Acid - Jain, Vipin Kumar; Kumar, Mrityunjay (SynOpen, 2019)
A very efficient synthetic route to (–)-bulgecinine and 5-epibulgecinine from an aldehyde derived from l-glutamic acid is reported. Proline-catalysed asymmetric α-hydroxylation reaction of an aldehyde is the key step in this synthesis, which is used to incorporate a hydroxyl group at the α-position to that aldehyde in good yield and with very high diastereoselectivity. Both (–)-bulgecinine and 5-epi-bulgecinine are synthesised from the same olefin via epoxidation followed by BF3·OEt2-catalyzed intramolecular cyclisation. This synthetic route can easily be extended for the synthesis of the enantiomer and other isomers of bulgecinine starting from an aldehyde derived from d-glutamic acid.
Keywords: asymmetric hydroxylation; organocatalysis; diastereoselectivity; glycopeptide; antibiotics